Progressive technology of connecting-rod production - A. S. Jazvinsky; N. D. Gilj; V. Ja. Shchukin; A. A. Gornostaj (Литьë и металлургия, 2002)
The process is characterized by high capacity, simplicity, universality and auxiliaries durability, high coefficient of metal using and low manufacturing power imputs.